2016
DOI: 10.1371/journal.pone.0149587
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Fractal Dimension in Healthy Ageing and Alzheimer’s Disease

Abstract: Brain activity is complex; a reflection of its structural and functional organization. Among other measures of complexity, the fractal dimension is emerging as being sensitive to neuronal damage secondary to neurological and psychiatric diseases. Here, we calculated Higuchi’s fractal dimension (HFD) in resting-state eyes-closed electroencephalography (EEG) recordings from 41 healthy controls (age: 20–89 years) and 67 Alzheimer’s Disease (AD) patients (age: 50–88 years), to investigate whether HFD is sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 55 publications
9
102
0
Order By: Relevance
“…In this case, the results show that HFD values for AD patients are lower than those for normal subjects. This result is consistent with the finding in other studies [46,80]. As with the TsEn, the differences between HFD biomarkers for AD patients and normal subjects for the EEG frequency bands (i.e., delta, theta, and alpha bands) were Fp1 Fp2 F7 F3 FZ F4 F8 T3 C3 CZ C4 T4 T5 P3 PZ P4 T6 O1 O2 EEG channel Whole EEG …”
Section: Resultsupporting
confidence: 92%
See 1 more Smart Citation
“…In this case, the results show that HFD values for AD patients are lower than those for normal subjects. This result is consistent with the finding in other studies [46,80]. As with the TsEn, the differences between HFD biomarkers for AD patients and normal subjects for the EEG frequency bands (i.e., delta, theta, and alpha bands) were Fp1 Fp2 F7 F3 FZ F4 F8 T3 C3 CZ C4 T4 T5 P3 PZ P4 T6 O1 O2 EEG channel Whole EEG …”
Section: Resultsupporting
confidence: 92%
“…In addition, HFD provides a more accurate measure of the complexity of signals compared to other methods [75,78,79] and it has been shown to be an efficient method for discriminating between AD patients and normal subjects [31,80]. HFD of the EEG is potentially a good biomarker of AD diagnosis as it is significantly lower in AD patients than in normal subjects [46,80,81]. Smits et al found that HFD is sensitive to neural changes selectively related to AD patients and normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Smits et al [29] showed calculations of FD in resting state EEG recordings from 67 AD patients and 41 healthy controls. They found the FD and signal complexity decreased with age in normal controls and that it further decreased in AD patients, especially in temporal-occipital regions [29]. This study supports the concept that brain signal FD correlates with changes in brain connectivity and complexity.…”
Section: Discussionmentioning
confidence: 99%
“…The signal complexity of EEG, a reflection of the irregularity of the wave shape and dynamics, is reported to be influenced by healthy aging and associated with brain disorders such as AD [73, 74]. Studies using fractal dimension demonstrated that resting-state EEG signal complexity increases from youth to maturity, followed by a reduction in healthy elderly.…”
Section: Eeg Signal Complexity and Agingmentioning
confidence: 99%
“…Studies using fractal dimension demonstrated that resting-state EEG signal complexity increases from youth to maturity, followed by a reduction in healthy elderly. These studies also provided evidence indicating that, in AD, the signal complexity is further reduced as cognitive function declines [73, 74]. …”
Section: Eeg Signal Complexity and Agingmentioning
confidence: 99%